Recent HIV infection rates among HIV positive patients seeking voluntary counseling and testing centers in the metropolitan region of Recife - Pe, Brazil - Cavalcanti,Ana Maria Salustiano (2012)
The BED capture enzyme immunoassay test makes it possible to determine whether individuals were recently infected with HIV. OBJECTIVE: In this study, the overall HIV and recent infections prevalences were determined at five Voluntary Counseling and Testing (VCT) centers, in the Metropolitan Region of Recife, Northeastern of Brazil. MATERIAL AND METHODS: A cross-sectional study was conducted among users of five VCTs in the metropolitan region of Recife between July 2007 and April 2009. Out of the individuals who tested positive for HIV, 169 were analyzed to assess the prevalence of recent infection by means of the BED-CEIA (BED-Calypte®). RESULTS: Out of 46,696 individuals tested 916 (1.96%) turned out positive for HIV infection The highest prevalence was in Recife (3.9%). The prevalence was higher among males (3.93%), and men who have sex with men (MSM) (12.4%). The frequency of recent infections among the 169 subjects evaluated was 23.7%. Recent infections were more common among individuals under 25 years of age. There was slight predominance of men and higher frequency of heterosexuals in both groups, but still a significant portion of MSM (33%). Subtype B predominated, followed by a high proportion of subtype F. CONCLUSIONS: Recent infection occurs mainly among young individuals and heterosexuals, despite a significant proportion of recent infection among MSM. These results suggest that preventive actions aimed at the MSM community remains a challenge and efforts focusing this group should continue to be a priority.